A Framework for Analysis and Development of Augmented Reality Applications in Science and Engineering Teaching - Valerie Czok; Manuel Krug; Sascha Müller; Johannes Huwer; Stefan Kruse; Wolfgang Müller; Holger Weitzel (Education Sciences, 2023)
As augmented reality (AR) becomes a promising technology for use in science and engineering teaching, the need for generally valid criteria and frameworks for the analysis, development, and setup of AR applications arises. In this article, we present an evaluations matrix to analyze current augmented reality approaches for life science teaching (biology, chemistry) and engineering and simultaneously provide directives for future augmented reality application designs. Based on an extensive literature review followed by focus group discussions with experts, the evaluation matrix combines domain-specific aspects, technical features, and subject and media didactical principles to determine seven select parameters. This ensures adequate coverage of the broad range of key considerations in the development of augmented reality technology for science and engineering teaching. Through cluster analysis, two groups of applications could be identified. The first group comprises applications whose development was more technology-driven. Applications in the second group take more didactic criteria into account and are to be considered more holistically from an instructional perspective. No correlation could be observed between the design of the AR application and the intended learning effects. The parameters derived for the evaluation matrix contribute to specifying relevant criteria for the development of AR applications.